The pterygopalatine fossa: morphometric CT study with clinical implications. - Vuksanovic-Bozaric, Aleksandra; Vukcevic, Batric; Abramovic, Marija; Vukcevic, Nemanja; Popovic, Natasa; Radunovic, Miroslav (Surgical & Radiologic Anatomy, 2019)
Purpose: The pterygopalatine fossa is a deep viscerocranial space containing the maxillary artery and nerve, the pterygopalatine ganglion, and the nerve of the pterygoid canal (vidian nerve). The endoscopic approach to this area relies on adequate preoperative imaging, such as computed tomography (CT). The aim was to determine the morphometric characteristics of the pterygopalatine fossa and its communications, including several previously unpublished measurements.Methods: 100 CT scans (56 male and 44 female patients) were analyzed. The axial, coronal, and sagittal slices, together with the three-dimensional reconstructions, were used in the study.Results: The central diameter and the length of the foramen rotundum, the vertical diameter and the length of the pterygoid (vidian) canal, and the diameter of the sphenopalatine foramen were significantly larger in men. The central diameters of the foramen rotundum and the vidian canal were significantly smaller than their anterior and posterior transverse diameters. The vidian canal length of 12.1 mm indicates the presence of the type 3 VC with a sensitivity of 83% and a specificity of 85%.Conclusion: Several new descriptions of the pterygopalatine fossa are presented here (such as the angle between the sphenopalatine foramen and the vidian canal, a new aspect in the understanding of the FR, and the distance between the posterior wall of the maxillary sinus to the vidian canal and the foramen rotundum), which might prove useful in the comprehension of the anatomy of the pterygopalatine fossa.